Moderating effects of social support on the relationship between substance use disorders and HIV viral load and medication adherence among Black women living with HIV in the United States. Issue 10 (3rd October 2022) - Reid, Rachelle; Dale, Sannisha K.
ABSTRACT: Substance use may predict lower rates of antiretroviral therapy (ART) adherence and viral suppression among Black Women Living with HIV (BWLWH). We assessed how perceived social support (PSS) moderates the relationship between substance use disorder (SUD) and viral load (VL) and ART adherence. 119 BWLWH provided information on PSS, SUD, alcohol use disorder (AUD) and adherence (via Wisepill). Higher PSS from friends ( β  = −.263, p  = .008) and significant others ( β  = −.219, p  = .025) predicted lower VL. SUD predicted low Wisepill adherence (a) in the past week ( β  = −.273, p  = .035) and past two weeks ( β  = −.273, p  = .033) only for women low in PSS from friends, and (b) in the past two weeks only for women low in total PSS ( β  = −.294, p  = .024). Ironically, for women high in total PSS, SUD predicted higher adherence in the past four weeks ( β  = .360, p  = .006). Adherence and VL may be bolstered by understanding the role of various forms of PSS and SUDs.